Three-way assessment of long-chain n-3 PUFA nutrition: by questionnaire and matched blood and skin samples - Wallingford, Sarah C. (2012)
The long-chain n-3 PUFA, EPA, is believed to be important for skin health, including roles in the modulation of inflammation and protection from photodamage. FFQ and blood levels are used as non-invasive proxies for assessing skin PUFA levels, but studies examining how well these proxies reflect target organ content are lacking. In seventy-eight healthy women (mean age 42·8, range 21–60 years) residing in Greater Manchester, we performed a quantitative analysis of long-chain n-3 PUFA nutrition estimated from a self-reported FFQ (n 75) and correlated this with n-3 PUFA concentrations in erythrocytes (n 72) and dermis (n 39). Linear associations between the three n-3 PUFA measurements were assessed by Spearman correlation coefficients and agreement between these measurements was estimated. Average total dietary content of the principal long-chain n-3 PUFA EPA and DHA was 171 (sd 168) and 236 (sd 248) mg/d, respectively. EPA showed significant correlations between FFQ assessments and both erythrocyte (r 0·57, P<0·0001) and dermal (r 0·33, P=0·05) levels, as well as between erythrocytes and dermis (r 0·45, P=0·008). FFQ intake of DHA and the sum of n-3 PUFA also correlated well with erythrocyte concentrations (r 0·50, P<0·0001; r 0·27, P=0·03). Agreement between ranked thirds of dietary intake, blood and dermis approached 50 % for EPA and DHA, though gross misclassification was lower for EPA. Thus, FFQ estimates and circulating levels of the dietary long-chain n-3 PUFA, EPA, may be utilised as well-correlated measures of its dermal bioavailability.